Hubungan Indeks Massa Tubuh dan Panjang Tungkai dengan Kecepatan pada Atlet Futsal SMA Negeri 1 Tempeh: Hubungan Indeks Massa Tubuh dan Panjang Tungkai dengan Kecepatan pada Atlet Futsal SMA Negeri 1 Tempeh - Khareswara Wiku Januarta; Noortje Anita Kumaat; Roy Januardi Irawan; Aprilyan Putra Bimantoro (Universitas Hamzanwadi, 2026)
Sprinting ability is an important physical component in futsal; however, research on the relationship between Body Mass Index (BMI) and leg length, in conjunction with sprint speed, among adolescent futsal athletes remains limited. This study aimed to determine the relationship between BMI and leg length and 30-meter sprint speed among futsal athletes at Tempeh State High School 1. The study employed a quantitative approach with a correlational design involving 20 subjects selected through total sampling. BMI data were obtained by measuring body weight and height; leg length was measured from the trochanteric point to the floor using an anthropometer; and sprint speed was measured using a 30-meter run test. Data analysis utilized Spearman’s Rho test because the BMI data were not normally distributed, along with partial correlation analysis for simultaneous relationships. The results showed a very strong and significant negative correlation between BMI and 30-meter sprint speed (rs = -0.944; p < 0.001) and between leg length and 30-meter sprint speed (rs = -0.996; p < 0.001). Partial correlation analysis showed that leg length had a stronger relationship (r = -0.935) with sprint speed than IMT (r = -0.714). It was concluded that anthropometric characteristics, particularly leg length, play a significant role in supporting sprint performance in futsal.